On the theory of hyper-$Q$-homeomorphisms - Kovtonyuk, D. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We show that if a homeomorphism $f$ of a domain $D ⊂ R^n,\; n ≥ 2$, is a hyper-$Q$-homeomorphism with $Q ∈ L_{\text{loc}^1$ , then $f ∈ ACL$. As a consequence, this homeomorphism has partial derivatives and an approximation differential almost everywhere.